The complete chloroplast genome sequence and phylogenetic analysis of Ranunculus kadzusensis Makino 1929, an endangered species in Korea - I-Jin Choi; Hey-Min Park; Wan-Hee Lee; Mi-Sung Park (Mitochondrial DNA. Part B. Resources)
Ranunculus kadzusensis Makino 1929 is one of the endangered endemic species on the Korean Peninsula. The complete chloroplast of R. kadzusensis is 158,301 bp in length with a typical quadripartite structure comprised of a large single-copy region (84,973 bp), a small single-copy region (17,638 bp), and two inverted repeat regions, each 27,845 bp in length. The overall GC content is 37.83%, the genome encoded a total of 113 genes, comprising 79 protein-encoding genes, 30 tRNA, and four rRNA genes. Phylogenetic analysis indicated that R. kadzusensis was closely related to Ranunculus pekinensis and Ranunculus bungei. This chloroplast genome enriches Ranunculus’s genome information and will also be valid for the species’ genetic classification in the family Ranunculaceae.